Ahmed glaucoma valve in vitrectomized eyes: An implantation technique to minimize early postoperative fluid-loss hypotony. Issue 5 (September 2021) - Arpa, Paolo; Arpa, Cristina
Purpose: To describe the application of a modified Ahmed glaucoma valve (AGV) surgical implantation technique in vitrectomized eyes, in order to minimize the risk of early postoperative hypotony, which leads to hemorrhagic complications. Materials and methods: Data of patients implanted with AGV using the surgical technique described were retrospectively reviewed. Inclusion criterion: glaucomatous eyes with previous history of pars plana vitrectomy. Intraocular pressure (IOP) measurement and ophthalmic examination were performed preoperatively and postoperatively weekly for 1 month for the detection of early hypotony, choroidal effusion/detachment, intraocular hemorrhage. The surgical technique consisted in creating a 5 mm long scleral tunnel with a 23 G needle reaching the anterior chamber at the iridocorneal angle, in which the Ahmed glaucoma valve tube was inserted. Results: Ten eyes of 10 patients were included. Median preoperative IOP was 30.5 mmHg [interquartile range (IQR) 28.3–33.0]; median postoperative IOP was 12.0 mmHg (IQR 9.3–13.0) at 1 week, and 12.5 mmHg (IQR 11.0–15.0) at 1 month. In no cases postoperative IOP was <8 mmHg. On the first postoperative day, five (50%) eyes showed few blood clots in the anterior chamber. On the second-week appointment, moderate choroidal effusion was observed in two eyes (20%). No hemorrhagic complications were observed. Conclusions: The creation of a long intrascleral tunnel with a 23 G needle for AGV implantation in vitrectomized eyes could be effective in decreasing leakage through the space between the valve tube and the sclerocorneal tissue. This technique is safe, easy to perform, feasible and fast. Due to its advantages and good postoperative results, it could also be adopted in non-vitrectomized eyes.